THE RELATION OF ISLAM AND IRAN; A CIVILIZATIONAL APPROACH - Mohsen alviri (تاریخ اسلام, 2004)
The theorists of civilization, have considered the diffrent factors which have a significant role in forming a civilization and sometimes they have paid attention to the role of the religious beliefs in the process of development and progress of civilization. But the factor of religion as the essence of civilization has not found its proper role among these theories. On the other hand the theologian thinkers and the sociologist of religion have offered the different opinions. If we consider civilization making in the sphere of guidance whic is the main responsibility of the religion, then we can talk about the efficiency of religion and religion teachings in the realm of civilization making and its requirements. Religious teachings in the sphere of civilization making, regardless of their efficiency, will not be successful if we apply them in an improper conditions, like the seeds in a tough ground. Studying the condition of Iran before and after the manifestation of Islam and also examining the Islamic united society befor and after the Iranian entrance into this society can help us in perceiving their relations. The historical studies indicates that Iran was one of the areas that Islam could prove its own capability for civilization making there. In a general view we can say the best service of Iran to Islam was preparing the suitable conditions for the manifestation of religion's power in civilization making, and one of the services of Islam to Iran was conducting the civilization of the people who lived in this territory.